Strategi Penguatan Mutu Keagamaan Masyarakat Gondosari Gebog Kudus - Masruroh, Evi Munifatul; Mas’udi, Mas’udi (Islamic Management and Empowerment Journal, 2025)
The purpose of this study was to determine the strategy for strengthening religious quality in the abangan community. This study uses a phenomenological approach to explore the strategy for strengthening religious quality in the abangan community in Dukuh Tulis, Gondosari Village. Data were collected through observation, interviews, and documentation. Although the majority of residents are Muslim, the practice of Kejawen is still strong and Islamic understanding is relatively low. Religious figures then apply strategies such as the Al Falah taklim assembly, Kalam Hikmah, Umat Damai Sejahtera, and dakwah bil hal to improve religious understanding and quality.